Investigating behavioral phenotypes related to autism spectrum disorder in a gene-environment interaction model of Cntnap2 deficiency and Poly I:C maternal immune activation - Haddad, Faraj L.; De Oliveira, Cleusa; Schmid, Susanne (Frontiers in Neuroscience, 2023)
Autism Spectrum Disorder (ASD) has been associated with a wide variety of genetic and environmental risk factors in both human and preclinical studies. Together, these findings support a gene-environment interaction hypothesis whereby different risk factors independently and synergistically impair neurodevelopment and lead to the core symptoms of ASD. To date, this hypothesis has not been commonly investigated in preclinical ASD models. Mutations in the Contactin-associated protein-like 2 (Cntnap2) gene and exposure to maternal immune activation (MIA) during pregnancy have both been linked to ASD in humans, and preclinical rodent models have shown that both MIA and Cntnap2 deficiency lead to similar behavioural deficits. In this study, we tested the interaction between these two risk factors by exposing wildtype, Cntnap2+/-, and Cntnap2-/- rats to Polyinosinic: Polycytidylic acid (Poly I:C) MIA at gestation day 9.5. Our findings showed that Cntnap2 deficiency and Poly I:C MIA independently and synergistically altered ASD-related behaviours like open field exploration, social behaviour, and sensory processing as measured through reactivity, sensitization, and prepulse inhibition (PPI) of the acoustic startle response. In support of the double-hit hypothesis, Poly I:C MIA acted synergistically with the Cntnap2-/- genotype to decrease PPI in adolescent offspring. In addition, Poly I:C MIA also interacted with the Cntnap2+/- genotype to produce subtle changes in locomotor hyperactivity and social behaviour. On the other hand, Cntnap2 knockout and Poly I:C MIA showed independent effects on acoustic startle reactivity and sensitization. Together, our findings support the gene-environment interaction hypothesis of ASD by showing that different genetic and environmental risk factors could act synergistically to exacerbate behavioural changes. In addition, by showing the independent effects of each risk factor, our findings suggest that different ASD phenotypes could be caused by different underlying mechanisms.